2015
DOI: 10.1152/jn.00845.2013
|View full text |Cite
|
Sign up to set email alerts
|

Speed-accuracy tradeoff by a control signal with balanced excitation and inhibition

Abstract: Lo CC, Wang CT, Wang XJ. Speed-accuracy tradeoff by a control signal with balanced excitation and inhibition. J Neurophysiol 114: 650-661, 2015. First published May 20, 2015 doi:10.1152/jn.00845.2013.-A hallmark of flexible behavior is the brain's ability to dynamically adjust speed and accuracy in decision-making. Recent studies suggested that such adjustments modulate not only the decision threshold, but also the rate of evidence accumulation. However, the underlying neuronallevel mechanism of the rate chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 75 publications
2
20
0
Order By: Relevance
“…Similar changes in LIP and prefrontal neurons have been shown to implement changes of decision bound for speed-accuracy tradeoff (Hanks et al, 2014; Heitz and Schall, 2012). Thus, our results contribute to mounting evidence that changes in decision bound are not implemented through elevated end-point as one might expect, but instead through mechanisms that directly accelerate or decelerate accumulation of evidence toward a fixed threshold (Hanks et al., 2014; Lo et al, 2015). …”
Section: Discussionsupporting
confidence: 60%
“…Similar changes in LIP and prefrontal neurons have been shown to implement changes of decision bound for speed-accuracy tradeoff (Hanks et al, 2014; Heitz and Schall, 2012). Thus, our results contribute to mounting evidence that changes in decision bound are not implemented through elevated end-point as one might expect, but instead through mechanisms that directly accelerate or decelerate accumulation of evidence toward a fixed threshold (Hanks et al., 2014; Lo et al, 2015). …”
Section: Discussionsupporting
confidence: 60%
“…But these parameters have very different implications for the underlying neural mechanisms. For example, adjustments in neural activity at the time of RT are associated with changes in the strength of cortico-striatal connections (Lo & Wang, 2006), whereas adjustments of the baseline may be implemented through background excitation and inhibition (Lo, Wang, & Wang, 2015). Although the measured onset time and growth rate of neural dynamics appear to be less diagnostic about specific underlying parameters, variation in measured neural baseline and neural activity at RT can be associated more directly with variation in the starting point and threshold parameters of accumulator models.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, SEF, like preSMA, monitors performance and exerts indirect influence on motor processes to adjust RT (Scangos et al, 2013;Stuphorn et al, 2010). Such indirect influence can be described as urgency, as suggested by others (e.g., Thura and Cisek, 2016), and implemented in abstract spiking network models (Lo et al, 2015). Earlier research showed that intracortical electrical microstimulation of sites in SEF can speed or slow RT according to task context (Stuphorn and Schall, 2006).…”
Section: New Insights Into Mechanisms Of Satmentioning
confidence: 99%